Metal or plastic stents for preoperative biliary drainage in resectable pancreatic cancer. Issue 12 (25th August 2015) - Tol, J A M G; van Hooft, J E; Timmer, R; Kubben, F J G M; van der Harst, E; de Hingh, I H J T; Vleggaar, F P; Molenaar, I Q; Keulemans, Y C A; Boerma, D; Bruno, M J; Schoon, E J; et al.
Abstract : Introduction: In pancreatic cancer, preoperative biliary drainage (PBD) increases complications compared with surgery without PBD, demonstrated by a recent randomised controlled trial (RCT). This outcome might be related to the plastic endoprosthesis used. Metal stents may reduce the PBD-related complications risk. Methods: A prospective multicentre cohort study was performed including patients with obstructive jaundice due to pancreatic cancer, scheduled to undergo PBD before surgery. This cohort was added to the earlier RCT (ISRCTN31939699 ). The RCT protocol was adhered to, except PBD was performed with a fully covered self-expandable metal stent (FCSEMS). This FCSEMS cohort was compared with the RCT's plastic stent cohort. PBD-related complications were the primary outcome. Three-group comparison of overall complications including early surgery patients was performed. Results: 53 patients underwent PBD with FCSEMS compared with 102 patients treated with plastic stents. Patients' characteristics did not differ. PBD-related complication rates were 24% in the FCSEMS group vs 46% in the plastic stent group (relative risk of plastic stent use 1.9, 95% CI 1.1 to 3.2, p=0.011). Stent-related complications (occlusion and exchange) were 6% vs 31%. Surgical complications did not differ, 40% vs 47%. Overall complication rates for the FCSEMS, plastic stent and early surgery groups were 51% vs 74% vs 39%. Conclusions: For PBD in pancreatic cancer, FCSEMS yield a better outcome compared with plastic stents. Although early surgery without PBD remains the treatment of choice, FCSEMS should be preferred over plastic stents whenever PBD is indicated. Trial registration number: Dutch Trial Registry (NTR3142).